Penguatan Karakter Pemuda di Desa Pacarejo, Kecamatan Semanu, Kabupaten Gunung Kidul melalui Pelatihan Baca Al-Qur'an - Widodo, Syukri Fathudin Achmad; Dardiri, Achmad; Marzuki; Anam, Ahmad Muzakkil; Rubiyanto, Yayan; Djainudin, Hamdhan (Jurnal Pengabdian dan Pemberdayaan Banyuwangi (Jurnal Abdiwangi), 2024)
Community service is an integral part of the "Tri Dharma" of higher education that must be carried out by lecturers, including those at Universitas Negeri Yogyakarta. This activity involves lecturers engaging with communities or industry partners outside the campus, aiming to maximize their expertise while addressing problems or optimizing the potential within society. This particular community service proposal adopts the "Mbangun Desa" (Building Villages) scheme, targeting human resource development with a specific focus on strengthening the character of youth. The program, titled "Strengthening the Character of Youth in Pacarejo Village, Semanu District, Gunung Kidul Regency Through this community service program, it is expected that youth in Pacarejo Village, Semanu, Gunung Kidul will improve their Qur'anic recitation skills and build strong character. Keywords: Character Strengthening, Youth, Qur'anic Recitation Art